Debit cards in Singapore - Koh, Ke Ching (2008)
The focus of this study is on teenagers and young adults who are the main customers of debit cards. The study aims to determine the factors, both antecedent variables and socialization agents, that have an influence on the ownership and usage of debit cards; and also identify the attributes in debit cards in general that are perceived to be important by consumers when deciding to subscribe to a debit card.